Different Doses of Calcium Supplementation to Prevent Gestational Hypertension and Pre-Eclampsia: A Systematic Review and Network Meta-Analysis - Chen, Dexin; Wang, Hong; Xin, Xing; Zhang, Long; Yu, Aihong; Li, Shuwen; He, Rongxia (Frontiers in Nutrition, 2022)
Abstract Objective Calcium supplementation prevents gestational hypertension and preeclampsia; however, current studies are controversial, and there is a paucity of evidence regarding the optimal dosing of calcium. Method Eight electronic databases of the Cochrane Library, PUBMED, Web of Science, EMBASE, WANGFANG, VIP, CBM, and CNKI will be searched. The retrieval deadline was July 2021. Two researchers independently screened the literature, extracted data, and evaluated the methodological quality according to the inclusion criteria. Results and Discussion Forty-eight studies were incorporated into the final analyses. The results showed that all of doses of calcium can reduce the incidence of gestational hypertension in low-risk population, and moderate dose can reduce the incidence of gestational hypertension in high-risk groups, however, moderate dose is the best (low-risk and high-risk population). Both moderate and high doses of calcium can reduce the incidence of preeclampsia in low-risk groups, however, moderate dose is the best. The authenticity and reliability of the above conclusions are reduced due to the limitations of contemporary studies in experimental design, result measurement, statistics and evidence quality. Therefore, high-quality studies with larger samples are still needed to further evaluate the effect of calcium supplementation in preventing gestational hypertension and preeclampsia.